IPod touch made simple - Trautschold, Martin (Apress ; Springer [distributor], 2010)
Presents an introduction to the features and functions of the iPod Touch, covering such topics as personalization, using iTunes, using Safari to access the Internet, downloading apps, making video calls over Wi-Fi, and troubleshooting.